Flow Akademik Ditinjau dari Persepsi Kompetensi Akademik dan Dukungan Guru pada Siswa SMA - Devi Hastiana; Nurul Hidayah (Universitas Ahmad Dahlan, 2021)
Academic Flow in Terms of Perceived Academic Competence and Teacher Support for High School StudentsÂ Academic flow has a very important role in the field of education to increase academic success. This study aims to examine the relationship between perceived academic competence and teacher social support with academic flow. The subjects of this study were all 92 students of SMA